Transformation of the reproduction of human capital in the context of the digital economy - Stryabkova, Elena Anatolievna; Lyshchikova, Julia Vladimirovna; Gerasimova, Natalya Anatolievna; Kulik, Anna Mihailovna; Weis, Elena Vladimirovna (Nexo Revista Científica, 2021)
The relevance of the study is determined by the fact that the processes of reproduction of human capital with the most recent quality characteristics, skills, and competencies are actively evolving in the context of the digital transformation of the economy. The goal of the article is to study transformation processes and to identify the main characteristics of the reproduction of human capital in the context of digital and technological transformation. The empirical base of the study is represented by the data from the Federal State Statistics Service of the Russian Federation, as well as from reports and statistical books of the National Research University Higher School of Economics on the development of human capital and digital economy in Russia. The methodological basis of the study includes a systemic and holistic approach, retrospective, evolutionary, monographic, and comparative logical analysis, content analysis of scientific literature and empirical sources, as well as methods of generalization and systematization. The stages of the evolution of human capital have been identified and described in the course of the study; a model of the evolution of the human capital structure in the digital economy has been formed, including its traditional and new characteristics; the physical, intellectual, socioindustrial, and digital (technological) components of the reproduction of human capital in the Russian Federation and the Central Federal District have been analyzed. The conclusion has been drawn of the need to transform the mechanisms of the reproduction of human capital for the formation of new digital and technological competencies and for overcoming the divergence of technogenesis and anthropogenesis.